2019
DOI: 10.18203/2394-6040.ijcmph20194631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training on coding accuracy of obstetrical diagnosis in Naili DBS Hospital

Abstract: Accurate billing is crucial for the financial health of medical institutions. Billing and coding are based on what services are documented by the provider and selection of the appropriate code is most commonly done by the provider or a coding specialist. 3 Medical coding is the transformation of healthcare diagnosis, procedures, medical services, and equipment into universal medical alphanumeric codes. It can be subsequently used for ABSTRACT Background: The accuracy of clinical coding is very important in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The reaction-level results revealed that the nurses were highly satisfied with the educational content, the training length, and the applications of this course in clinical work [ 26 ]. Oashttamadea has also noted the significant role of training in improving the accuracy of delivery coding [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction-level results revealed that the nurses were highly satisfied with the educational content, the training length, and the applications of this course in clinical work [ 26 ]. Oashttamadea has also noted the significant role of training in improving the accuracy of delivery coding [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Alonso, the main obstacles to ensuring the quality of coded data are the clinical coders’ limited understanding of the medical terminology, the clinical coders’ experience, or problems within health records, e.g., a lack of specificity of the recorded data or imperfections of the classification system [ 10 ]. Clinical Coders are responsible for the accuracy, completeness, and timeliness of the allocated codes, factors that ensure the quality of coding [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation